Improvement of the classification process for the digitization of document archives based on the Balanced Scorecard management system. - Bolaños Jijón, Alexis Fernando; Ladines Suco, Edison Rubén (Ingeniería Química y Desarrollo, 2022)
Globally, technological advances and the growing need for increasingly comprehensive databases containing sufficient amounts of historical data to be stored have driven initiatives such as archival digitization and actual document storage. From large corporations to government organizations, what began as an opportunity for improvement has now become a growing need. Digitizing information implies not only having technological tools and virtual and cybernetic capabilities, but also having the appropriate personnel with a deep knowledge of the process and adequate training in document and storage techniques, depending on the type of information to be digitized. The digitization process involves several phases: archiving, barcode identification, classification, scanning and data entry of the documents. The objective of this research is to design a management model using the Balanced Scorecard tool to improve the process of classification of document archives in order to increase customer satisfaction.
Keywords: Digitization; Ishikawa Diagram; Deming Cycle; Balanced Scorecard